Labor Reallocation in Transitional Economies--Twenty Years Later - Pauna, Catalin (2012)
The paper investigates labor reallocation across main economic sectors between 1989 and 2007 in the CEE2 countries, now all members of the EU, using a methodology presented in Jackman and Pauna (1997). Defining a series of indices aimed at capturing the speed, magnitude and efficiency of employment reallocation, the work assesses the extent to which these countries have succeeded in converging towards distributions of sectoral employment similar to those in the old EU members. The work shows that, overall, the CEE countries have made progress towards reallocating jobs from the oversized labor intensive sectors, characteristic of the early years of transition, such as agriculture and heavy industries, towards the services sector. However, convergence has been relatively slow and its pace has been different from country to country. Bulgaria emerges as the country where the fastest restructuring has taken place, and in the right direction. Romania, in particular, appears to have made least progress, although it is also moving in the right direction. The still large agricultural sector, which continued to hire around 30% of the occupied population in 2007, remains an area which will require further and massive restructuring. As of 2007, in the case of Romania, around 40% of the jobs expected to be created in the growing sectors, computed by benchmarking actual job destruction and job creation against the comparator economy, have occurred. The figure increases to over 50%, when the distortive effect of agriculture is removed. At the same time, over 90% of the job destruction and creation took place in the appropriate direction, towards the comparator EU employment distribution.